Predictors of ventricular tachyarrhythmia in patients with a wearable cardioverter defibrillator: an international multicenter registry - Kreimer, Fabienne; Koepsel, Katharina; Gotzmann, Michael; Kovacs, Boldizsar; Dreher, Tobias C.; Blockhaus, Christian; Klein, Norbert; Kuntz, Thomas; Shin, Dong-In; Lapp, Hendrik; Rosenkaimer, Stephanie L.; Abumayyaleh, Mohammad S. A.; et al. (Journal of interventional cardiac electrophysiology, 2024)
Wearable cardioverter defibrillator (WCD) can protect patients from sudden cardiac death due to ventricular tachyarrhythmias and serve as a bridge to decision of definite defibrillator implantation. The aim of this analysis from an international, multicenter WCD registry was to identify predictors of sustained ventricular tachycardia (VT) and/or ventricular fibrillation (VF) in this population.
Online veröffentlicht: 10. Juli 2024
Gesehen am 13.02.2025